MRI of iron oxide nanoparticles and myeloperoxidase activity links inflammation to brain edema in experimental cerebral malaria - Hoffmann, Angelika; Pfeil, Johannes; Müller, Ann-Kristin; Helluy, Xavier; Heiland, Sabine; Bendszus, Martin; Breckwoldt, Michael O. (Radiology, 2019)
PurposeTo investigate the association of inflammation and brain edema in a cerebral malaria (CM) mouse model with a combination of bis-5-hydroxy-tryptamide-diethylenetriaminepentaacetate gadolinium, referred to as MPO-Gd, and cross-linked iron oxide nanoparticle (CLIO-NP) imaging.Materials and MethodsFemale wild-type (n = 23) and myeloperoxidase (MPO) knock-out (n = 5) mice were infected with the Plasmodium berghei ANKA strain from May 2016 to July 2018. Seven healthy mice served as control animals. At a Rapid Murine Coma and Behavioral Scale (RMCBS) score of less than 15, mice underwent MRI at 9.4 T and received adodiamide, MPO-Gd, or CLIO-NPs. T1-weighted MRI was used to assess MPO activity, and T2*-weighted MRI was used to track CLIO-NPs. Immunofluorescent staining and flow cytometric analyses characterized CLIO-NPs, MPO, endothelial cells, and leukocytes. An unpaired, two-tailed Student t test was used to compare groups; Spearman correlation analysis was used to determine the relationship of imaging parameters to clinical severity.ResultsMPO-Gd enhancement occurred in inflammatory CM hotspots (olfactory bulb rostral migratory stream > brainstem > cortex, P < .05 for all regions compared with control mice; mean olfactory bulb signal intensity ratio: 1.40 ± 0.07 vs 0.96 ± 0.01, P < .01). The enhancement was reduced in MPO knockout mice (mean signal intensity ratio at 60 minutes: 1.13 ± 0.04 vs 1.40 ± 0.07 in CM, P < .05). Blood-brain barrier compromise was suggested by parenchymal gadolinium enhancement, leukocyte recruitment, and endothelial activation. CLIO-NPs accumulated mainly intravascularly and at the vascular endothelium. CLIO-NPs were also found in the choroid plexus, indicating inflammation of the ventricular system. Blood-cerebrospinal fluid barrier breakdown showed correlation with brain swelling (r2: 0.55, P < .01) and RMCBS score (r2: 0.75, P < .001).ConclusionIron oxide nanoparticle imaging showed strong inflammatory involvement of the icrovasculature in a murine model of cerebral malaria. Furthermore, bis-5-hydroxy-tryptamide-diethylenetriaminepentaacetate gadolinium imaging depicted parenchymal and intraventricular inflammation. This combined molecular imaging approach links vascular inflammation to breakdown of the blood-brain barrier and blood-cerebrospinal fluid barrier that correlate with global brain edema and disease severity.© RSNA, 2018Online supplemental material is available for this article.See also the editorial by Kiessling in this issue.
Published online: 4 December 2018
Gesehen am 02.04.2019